Provisions Of Murabahah Law With Bai' Bistaman Ajil (BBA) According To MUI Fatwa NO. 04/DSN-MUI/IV/2000 Concerning Murabahah And Its Implementation In BTPN Syari'ah Cab. Nibung Bay, Tanjung Balai - Sri Sudiarti; Hafsah Hafsah; Dina Fatma Sucitra Manullang (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
This study about how the implementation of Murabahah financing with the Bai' Bistaman 'Ajil contract at BTPN Syariah Cab. Teluk Nibung, Tanjung Balai City. The DSN-MUI Fatwa has regulated the financing in the MUI Fatwa No. 04/DSN-MUI/IV/2000 Regarding Murabaha. This research is using qualitative research or field research (Field Research) with a legal and conceptual approach. The data sources are primary and secondary data, data collection techniques are observation, interviews and documentation and analyze data using triangulation of sources, techniques and time. The results of the study are basically the law of murabahah financing and the bai' bistaman ajil contract is permissible. Islam has also regulated murabahah and bai' bistaman 'ajil in detail where in its application there are provisions and terms and pillars which have also been regulated in the MUI Fatwa. However, when one of the conditions and pillars is not fulfilled, it can damage the contract and change the law. Murabahah financing with BBA contract provided by BTPN Syariah Cab. Teluk Nibung in its application does not meet the financing provisions that have been regulated in the MUI Fatwa No. 04/DSN-MUI/IV/2000.